2014
DOI: 10.1167/iovs.13-13408
|View full text |Cite
|
Sign up to set email alerts
|

Eye Movements and Reading Speed in Macular Disease: The Shrinking Perceptual Span Hypothesis Requires and Is Supported by a Mediation Analysis

Abstract: Results are consistent with the shrinking perceptual span hypothesis: reading speed decreases with the average number of letters traversed on each forward saccade, an effect fully mediated by the total number of fixations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
46
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 57 publications
9
46
1
Order By: Relevance
“…In that study, the authors examined the relationship between reading speed and three oculomotor characteristics: fixation rate, forward saccade ratio and letters per forward saccade, and found that only the number of letters per forward saccade shows a strong positive correlation with reading speed. The effect of reduced number of letters per forward saccade on reading speed is consistent with the shrinking visual span hypothesis . More recently, Calabrèse et al .…”
Section: Visual Factors Limiting Reading In Macular Diseasesupporting
confidence: 77%
“…In that study, the authors examined the relationship between reading speed and three oculomotor characteristics: fixation rate, forward saccade ratio and letters per forward saccade, and found that only the number of letters per forward saccade shows a strong positive correlation with reading speed. The effect of reduced number of letters per forward saccade on reading speed is consistent with the shrinking visual span hypothesis . More recently, Calabrèse et al .…”
Section: Visual Factors Limiting Reading In Macular Diseasesupporting
confidence: 77%
“…15% (median 13%, range 2% to 34%). This increase in visual span is consistent with the hypothesis that reading speed is associated with the size of the visual span [10]. …”
Section: Resultssupporting
confidence: 90%
“…They showed that for lateral PRLs, the size of the visual span is indeed decreased by the presence of the scotoma. It is hypothesized that reading speed is determined in part by the size of the visual span [8, 9]: a reduced visual span increases the reading time (and therefore, decreases reading speed) by increasing the number of fixations [10]. We might expect people with PRLs lateral to a scotoma to have a smaller horizontal visual span, and as a result, to experience slower reading speed with horizontal text.…”
Section: Introductionmentioning
confidence: 99%
“…Mediation analyses or models are statistical tools to help understand or explain the underlying relationship between an independent and a dependent variable, by including a third explanatory variable. The analyses are commonly used in social psychological research but have recently been applied to vision research (Calabrèse et al, 2014). Interested readers should refer to Calabrèse et al (2014) for an excellent description and explanation of the mediation analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The analyses are commonly used in social psychological research but have recently been applied to vision research (Calabrèse et al, 2014). Interested readers should refer to Calabrèse et al (2014) for an excellent description and explanation of the mediation analysis. Figure 6 is a schematic depiction of the model, listing the relationship between the independent variable (error magnitude or amplitude of microsaccades), the dependent variable (acuity) and the third explanatory variable, or, the mediator variable (fixation stability).…”
Section: Discussionmentioning
confidence: 99%